Alterações nas funções de neutrófilos associadas a dependência ao crack - Funchal, Giselle Afonso (2021)
Crack-cocaine use disorder (CUD) has been associated with a higher incidence of infections, evidencing possible changes in innate immunity, which is responsible for the initial response to fighting infections. Women are more vulnerable to chronic complications in substance use disorders, often experiencing an intense feeling of withdrawal and consuming higher amounts of drugs than men. The aim of this work was to investigate whether CUD impacts neutrophil functionality. Peripheral blood samples and clinical data were collected at the beginning of detoxification treatment from 41 women with CUD and 31 healthy, non-user (HC) control women. Plasma cytokines were evaluated by flow cytometry and patients with CUD had higher levels of pro-inflammatory (TNF-α, IL-1β, IL-6, IL-8, IL-12) and regulatory (IL-10) cytokines compared to the HC group. Neutrophils were isolated and the phagocytosis was evaluated by flow cytometry with E. coli bioparticles. The production of Neutrophil Extracellular Traps (NETs) was evaluated through the quantification of dsDNA and later visualized and characterized by immunofluorescence. Patients with CUD had a higher basal rate of phagocytosis and increased production of NETs in vitro compared to HC subjects. These data demonstrate that the chronic use of crack activates the formation of NETs, a relevant inflammatory process. It should be noted that the basal activation levels (without stimulation) of neutrophils in patients corresponded to stimulated ones in controls. Furthermore, CUD neutrophils did not allow for greater LPS-induced activation of phagocytosis or NETs. We can infer that these functions are thus impaired in patients with CUD facing infections. Patients with CUD showed increased levels of intracellular reactive oxygen species (ROS) and activation of mitogen-activated protein kinases (MAPK), p38-p, AKT-p and ERK-p, which are essential steps in the signaling pathway for the formation of NETs. In addition, we observed a negative correlation between years of crack-cocaine use and AKT activation, as well as a negative correlation between substance use severity and NET formation. In conclusion, our study reinforces that the use of the substance cocaine-crack activates neutrophils in an inflammatory environment.